Synthesis of calcium-phosphorous doped TiO2 nanotubes by anodization and reverse polarization: A promising strategy for an efficient biofunctional implant surface - Alves, Sofia A.; Patel, Sweetu B.; Sukotjo, Cortino; Mathew, Mathew T.; Filho, Paulo N. [UNESP]; Celis, Jean-Pierre; Rocha, Luís A. [UNESP]; Shokuhfar, Tolou (Elsevier, 2017)
The modification of surface features such as nano-morphology/topography and chemistry have been employed in the attempt to design titanium oxide surfaces able to overcome the current dental implants failures. The main goal of this study is the synthesis of bone-like structured titanium dioxide (TiO2) nanotubes enriched with Calcium (Ca) and Phosphorous (P) able to enhance osteoblastic cell functions and, simultaneously, display an improved corrosion behavior. To achieve the main goal, TiO2 nanotubes were synthetized and doped with Ca and P by means of a novel methodology which relied, firstly, on the synthesis of TiO2 nanotubes by anodization of titanium in an organic electrolyte followed by reverse polarization and/or anodization, in an aqueous electrolyte. Results show that hydrophilic bone-like structured TiO2 nanotubes were successfully synthesized presenting a highly ordered nano-morphology characterized by non-uniform diameters. The chemical analysis of such nanotubes confirmed the presence of CaCO3, Ca3(PO4)2, CaHPO4 and CaO compounds. The nanotube surfaces submitted to reverse polarization, presented an improved cell adhesion and proliferation compared to smooth titanium. Furthermore, these surfaces displayed a significantly lower passive current in artificial saliva, and so, potential to minimize their bio-degradation through corrosion processes. This study addresses a very simple and promising multidisciplinary approach bringing new insights for the development of novel methodologies to improve the outcome of osseointegrated implants.
Keywords: Anodization; Bio-functionalization; Calcium-phosphorous surface; Osseointegrated implants; Reverse polarization; TiO2 nanotubes